Theoretical and methodological foundations of the physical rehabilitation technology of children 5-6 years old, with functional disorders of the support-motional apparatus - Kashuba, Vitaliy; Nosova, Natalia; Kozlov, Yuri (Journal of Education, Health and Sport, 2017)
Actuality. Preschool age is an important stage in the child’s personality formation, in the motor skills formation, in the development of physical qualities and in the provision of conditions for normal biological development. The child’s organism is subjected and varied to various external factors, both negative and positive, which have a significant influence on its development. The most important factor of external influence on the child’s organism is regular physical exercises, and the exercises of physical culture which are built methodically correctly affect favorably their physical development and health promotion. Research objective: to develop a technology for the prevention and correction of non-fixed disorders in support-motional apparatus of children aged 5–6 years with physical rehabilitation using under the conditions of preschool educational establishments. Research results. The technology was developed taking into account the individual child’s characteristics: the significance level and plane of posture disorder, the peculiarities of the varus or valgus deformity of the lower extremities and the flatfoot form, the consistent patterns between them; results of test tasks; associated diseases; the ability to learn new exercises, which allows to increase the effectiveness of the impact and to reduce the volume of applied means. The functional diagram of the prevention and correction technology of non-fixed disorders in child’s support-motional apparatus in senior preschool age makes it possible to display it from the position of a system-structural approach. The physical rehabilitation technology in the conditions of preschool educational institutions for children 5-6 years old includes theoretical lessons (thematic fairy tales), morning hygienic gymnastics, correctional exercises as part of physical education lesson, physical cultural pauses, therapeutic gymnastics, massage and physical therapy elements. All impacts were carried out in the game form. Conclusions. The physical rehabilitation technology for children 5-6 years old with non-fixed disorders in support-motional apparatus is built with consideration of the variable and basic components depending on the revealed correlation interconnection between posture disorders in the frontal and sagittal planes and spring-support function of the feet. It allows to differentiate the program of rehabilitation measures and to reduce significantly their volume without loss of efficiency. Prospects for further research are related to the development and implementation of the correction and prevention concept of functional disorders within the child’s support-motional apparatus in senior preschool age during the physical rehabilitation process.